Cooperative Learning With and About Internet Forums: A Case Study on a Unit on the Consumption and Chemistry of Mineral Water vs. Tap Water - Dittmar, Johanna; Eilks, Ingo (Frontiers in Education, 2022)
In today’s society, digital media play an increasing role in gathering and exchanging information. A growing part of communication takes place in the Internet and many people are increasingly influenced by information provided via digital and social media. Development of critical media literacy is needed, if the general public is expected to effectively deal with this flood of information and to become able to distinguish between correct and false information sources. Thus, critical media education becomes an important aim of education in general, and of chemistry education in particular when considering questions directly related to chemistry and its associated consumer products or technologies. The article describes a curriculum development case study investigating the integration of media education with chemistry learning along the case of learning with and about Internet forums on the topic of water chemistry. A unit integrating theoretical and practical chemistry learning based on student communication is described, which is built around a digital forum operated by Moodle. The unit design and findings from the implementation are presented.